From public to private safety regulation? The case of negotiated agreements in the French fresh produce import industry. (19th March 2007) - Codron, Jean-Marie; Fares, M'hand; Rouviere, Elodie
Recent EU law of safety self-regulation by firms leads French fresh produce importers to negotiate with public authorities a collective self-monitoring safety agreement. This paper is a case study of such an agreement in the Perpignan import market. Its actual design poses a problem of incentive alignment as long as it does not fit in with theoretical conditions. Empirical evidence and two complementary bodies of the literature are used to deal with this issue. Firstly, drawing on the literature of incentive schemes in teams, we show that implementing a collective discipline within the group is highly unlikely. Secondly, by turning to the literature of voluntary approaches to food safety, we show that conditions for efficient enforcement are not met either. By introducing supermarkets as a third party we propose an enriched framework, which allows a better understanding of why importers abide by the agreement and allocate resources in safety control.